1995
DOI: 10.1002/actp.1995.010460405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of equation‐of‐state parameters from PVT data

Abstract: The characteristic parameters for three different equation-of-state (EOS) theories have been determined for polystyrene and low-molecular weight polyisoprene using pressure-volume-temperature (PVT) data. Basically two procedures for the calculation of characteristic parameters were applied. The characteristic parameters were calculated, firstly, from coeficients of expansion, compressibilities and densities, and secondly, by fitting the corresponding EOS to PVT data minimizing the sum of the squares of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…see [9][10][11][12]. However, the P*, T*, V* values published by various authors for supposedly the same polymer are different.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…see [9][10][11][12]. However, the P*, T*, V* values published by various authors for supposedly the same polymer are different.…”
Section: Introductionmentioning
confidence: 96%
“…In addition Tait empirical relation has been used [8]. Curro [9], Zoller [10], Rodgers [11], Rudolf et al [12], reviewed and evaluated the suitability of several eos to describe the PVT behavior. Of the six mentioned theoretical expressions [11] the two: Dee and Walsh (D-W) modified cell model (MCM) [7], and Simha and Somcynsky (S-S) latticehole theory [4] performed well.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Tait empirical relation for seawater density also has been used 9. Curro,10 Zoller,11 Rodgers,12 and Rudolf et al13 reviewed and evaluated the suitability of several EOS to describe the PVT surface within the liquid state. The Simha–Somcynsky ( S –S) theory4 was found to well describe the PVT dependencies,14–18 as well as to provide good measure of the internal pressure, surface tension, cohesive energy density, or solubility parameters 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…d is defined through characteristic parameters for EOS theories can be obtained from pressure-volume-temperature (PVT) measurements. 8 In order to quantify the…”
Section: Introductionmentioning
confidence: 99%
“…8 Graessley et al showed that the SPC can be I. The polymerization procedure using homogeneous metallocene/methylalumoxane catalyst applied successfully in order to describe or predict the miscibility behavior of several binary polysystems was described elsewhere.…”
mentioning
confidence: 98%